Interaction of information and control systems: How the perception of behavior control affects the motivational effect of relative performance information - Schedlinsky, Ivo; Schmidt, Maximilian; Wöhrmann, Arnt (Accounting, Organizations and Society, 2020)
This study investigates the motivational effect of relative performance information (RPI) under working environments with or without surveillance, i.e., a behavioral control. We predict that surveillance negatively affects the performance-increasing effect of providing RPI and conduct a laboratory experiment to test this prediction. We manipulate surveillance by having participants work either with or without video surveillance. Consistent with our prediction, we find that the motivational effect of RPI diminishes if surveillance is present. Furthermore, we investigate the underlying mechanisms that drive our results. In particular, we find that surveillance increases perceived behavior control, eliciting individuals to perceive RPI more as a control mechanism. Our findings have important implications for firms using RPI and reveal the need to further investigate the effectiveness of incentive systems under behavior controls.